Potential of the Ethanol Extract of Luffa Leaves in Streptozotocin-Induced Diabetic Wistar Rats - Ogana Moses Miracle; Isaac John Umaru; Philip Shadrach (African Journal of Biochemistry and Molecular Biology Research, 2026)
Diabetes mellitus is a chronic metabolic disorder associated with hyperglycemia, dyslipidemia, oxidative stress, and progressive damage to vital organs. This study investigated the antidiabetic and biochemical effects of ethanol extract of Luffa acutangula leaves in streptozotocin-induced diabetic Wistar rats. Fresh leaves of Luffa acutangula were collected, authenticated, air-dried, pulverized, and extracted with 95% ethanol using maceration. Twenty-five adult male Wistar rats were randomly assigned to five groups: normal control, diabetic control, diabetic rats treated with metformin, and diabetic rats treated with 200 mg/kg and 400 mg/kg ethanol extract of Luffa acutangula leaves. Diabetes was induced through a single intraperitoneal injection of streptozotocin at 50 mg/kg body weight, and treatments were administered orally for 14 days. Blood glucose levels, liver function enzymes, bilirubin fractions, serum proteins, kidney function markers, electrolytes, and lipid profile parameters were evaluated. The findings showed that streptozotocin induction increased blood glucose levels, liver enzymes, renal biomarkers, and lipid abnormalities in diabetic rats. Treatment with Luffa acutangula leaf extract reduced blood glucose levels from 210.20 ± 7.30 to 140.50 ± 10.60 mg/dL at 200 mg/kg and from 198.60 ± 7.80 to 130.40 ± 9.80 mg/dL at 400 mg/kg. The extract also improved selected liver function markers, reduced creatinine levels, and ameliorated lipid profile disturbances, particularly total cholesterol and triglycerides. However, the elevated urea levels observed in extract-treated groups indicate the need for further renal safety evaluation. Overall, ethanol extract of Luffa acutangula leaves demonstrated promising antihyperglycemic, hepatoprotective, and hypolipidemic effects in diabetic rats, providing preclinical evidence for its potential relevance in managing diabetes-related metabolic complications.